The effectiveness of personal development opportunities at the Hong Kong Institute of Vocational Education (Tsing Yi) - Leung, Sui Man Anita (2008)
Personal development is the cornerstone of lifelong learning and academic and professional achievement. Co-curricular activities are good learning opportunities and support people to develop. A thorough review and examination of personal development education at HKIVE is needed so that new generations of students can more effectively learn and achieve their goals, enabling them to meet the crucial challenges of the 21st century.